The mediating effect of brand personality on the relationship between online atmospherics and attitudes toward the site - Zotos, Yorgos; Tsichla, Eirini; Hatzithomas, Leonidas; Boutsouki, Christina (My University, 2011)
The tremendous development of websites by a multitude of retail stores and service providers reinforced the need for optimal website design in order to attract the interest of surfers and potential consumers. This paper investigates the online atmosphere and brand personality interface. A laboratory experiment enabled the researchers to manipulate the low task relevant cues from a Museum’s website. The study findings support the positive influence of low-task relevant cues on attitudes toward the site and on surfers’ perceptions of brand personality. Moreover, the results bring to light a mediating effect of brand personality on consumers’ attitudes toward the site, suggesting a new approach regarding the examination of the particular variables.
Keywords: Mediating effect; Brand personality; Online atmospherics